The last noble gendarme : how the Tsar's last head of security and intelligence tried to avert the Russian Revolution - Marinich, Vladimir (State University of New York, 2021)
"Gripping account of the life of the Russian Tsar's last chief of security and intelligence"-- Provided by publisher.
Keywords: Globachev, K. I. -- (Konstantin Ivanovich), -- 1870-1941.; Globacheva, Sofia Nikolaevna.; Globachev family.; Russia. -- Okhrannyi͡a otdi͡elenīi͡a -- Biography.; Globachev family; Globachev, K. I. -- (Konstantin Ivanovich), -- 1870-1941; Globacheva, Sofia Nikolaevna; Russia. -- Okhrannyi͡a otdi͡elenīi͡a; Secret service -- Russia -- History -- 20th century.; Political culture -- Russia (Federation) -- Saint Petersburg -- History -- 20th century.; Immigrants -- New York (State) -- New York -- Biography.; Russians -- New York (State) -- New York -- Biography.; Soviet Union -- History -- Revolution, 1917-1921.; Saint Petersburg (Russia) -- Biography.; Service secret -- Russie -- Histoire -- 20e siècle.; Russes -- New York (État) -- New York -- Biographies.; URSS -- Histoire -- 1917-1921 (Révolution); Immigrants; Political culture; Russians; Secret service; New York (State) -- New York; Russia; Russia (Federation) -- Saint Petersburg; Soviet Union; 1900-1999; Biographies; History